(untitled) (Raparin Journal of Humanities (RJH), 2025)
This research aims to examine the Conflicts in the novel “Jano You Are My Story” by Maysaloun Hadi who is regarded as one of the most significant writers in the Arabic era. The novel focuses on three key types of conflicts within the work, which are; political, social, and religious concepts. At first, I elaborate on the concept of conflict throughout the work in terms of what meaning it conveys and its importance. Later, explaining how these conflicts can have impacts on humans and drive them to achieve their goals or defend against their interests. However, the novel begins with a broad overview of conflicts and its functions in literature. Overall, it depicts how the contemporary Arabic literature’s portrayal of issues such as conflict and loss demonstrate that art and reflection of reality and aesthetics. They influence on how more parties attempt to accomplish a goal which is common among humans to feel their integrity. In fiction, these political, social, and religious conflicts can result in an impactful tension that affects both individuals and society. According to Maysaloun Hadi, and among other aspects of the story, conflict is a crucial component that shapes events and the characters’ difficulties. To mention, place is more than just a location in her novels; it generally has a big influence on the protagonists’ outcomes.